Antibacterial and Anti-Biofilm Activities of Acetone Extracts of Usnea sp. against Mixed Cultures of Bacteria from Soak Liquor Samples and Tank Surfaces - (:unkn) unknown (AMER LEATHER CHEMISTS ASSOC, 2020)
Long-term or improper use of antibacterial agents utilized in the soaking process has led to the resistance of some bacteria in the leather industry. New agents may be the solution to combat these antibacterial resistant bacteria in the soaking process. As a natural resource, lichens are known to have many biological activities. In previous studies, we demonstrated that the acetone extracts of several lichen species including Usnea sp. may have potential antibacterial and anti-biofilm properties against some Bacillus species, which were isolated from different soak liquor samples. In the present study, it was questioned whether the same bioactivities of acetone extracts of Usnea sp. can be seen in the mixed cultures of tank surface samples and pre-and main soak liquor samples, which were obtained from different tanneries. Although the extracts did not show noteworthy antibacterial effect against one of the tank surface samples (inhibition ratios; 6.5-16.22%), inhibition percentages were detected as 69.32 and 46.33 at the concentrations of 240 and 120 mu g/mL for the other tank surface sample. The anti-biofilm potential of the extracts was tested on the sample where the antibacterial activity of the extracts was not observed. One of the mixed culture of samples from the tank surface could not be inhibited by the extracts in terms of bacterial growth. However, the extracts were tested on this biofilm-forming sample and detected more than 50% inhibition. Furthermore, the extracts inhibited the growth of the mixed culture of bacteria from pre-soak liquor by the percentages of 78.96, 61.5, 51.3, 45.1, and 33.4 at the concentrations of 240, 120, 60, 30 and 15 mu g/mL, respectively. On the other hand, the same antibacterial efficacy could not be observed in the other mixed culture from presoak liquor sample obtained from a different tannery whereas this sample formed a biofilm structure. The mixed culture of samples from the main soaking process was inhibited by the extracts at the inhibition percentages of 62.13-78.17 at the concentrations of 240- 30 mu g/mL. Similar results were also obtained for the other sample (64.6-76.5%) from main soak liquor sample obtained from a different tannery. In conclusion, lichen extracts may have potential antibacterial and anti-biofilm properties against the mixed culture of bacteria from tank surface, pre-and main soak liquor samples and maybe alternatively utilized in the leather industry.
Keywords: GRAM-NEGATIVE BACTERIA; TO-CELL COMMUNICATION; LEATHER; MICROORGANISMS; POPULATIONS; CHLORIDE; HIDES; SALT